The Effect of Social Support on Adversity Quotient in Generation Z Elementary School Teachers in Medan City - Zahira Haq, Khadijah (ATTA`DIB, 2025)
This research was conducted on 166 elementary school teachers (SD) Generation Z, aged 24 to 30, in Medan, with at least one year of teaching experience. This study aims to see the influence of social support felt by the teacher in increasing the adversity quotient (AQ). This is necessary to help Generation Z elementary school teachers be able to face the challenges of their work. The research method used is quantitative with purposive sampling. Research shows the influence of social support on the adversity quotient of Generation Z elementary school teachers in Medan. The support dimension of the principal and fellow teachers contributes the most to increasing the adversity quotient.